Ask Question
1 April, 22:54

Rewrite each expression by completing the square.

a. z^2 - 5z + 8

b. x^2 + 0.6x + 1

+2
Answers (1)
  1. 2 April, 00:23
    0
    The answer to your question is below

    Step-by-step explanation:

    a)

    z² - 5z + 8

    Equal to zero z² - 5z + 8 = 0

    Subtract 8 in both sides z² - 5z + 8 - 8 = 0 - 8

    Simplify z² - 5z = - 8

    Divide - 5 by 2 write the result

    in both sides of the equation z² - 5z + (-5/2) ² = - 8 + (-5/2) ²

    to the power of 2

    Simplify z² - 5z + 25/4 = - 8 + 25/4

    z² - 5z + 25/4 = - 32/4 + 25/4

    z² - 5z + 25/4 = - 7/4

    Factor (z - 5/2) ² = - 7/4

    b)

    x² - 0.6x + 1

    Convert 0.6 to a fraction 0.6 = 6/10 = 3/5

    x² - 3/5x + 1

    Equal to zero x² - 3/5x + 1 = 0

    Subtract - 1 in both sides z² - 3/5z + 1 - 1 = 0 - 1

    Simplify z² - 3/5z = - 1

    Divide - 3/5 by 2 write the result

    in both sides of the equation z² - 3/5z + (-3/10) ² = - 1 + (-3/10) ²

    to the power of 2

    Simplify z² - 3/5z + 9/100 = - 1 + 9/100

    z² - 3/5z + 9/100 = - 100/100 + 9/100

    z² - 3/5z + 9/100 = - 91/100

    Factor (z - 3/10) ² = - 91/100
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “Rewrite each expression by completing the square. a. z^2 - 5z + 8 b. x^2 + 0.6x + 1 ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers